PENGARUH PERBEDAAN TANAMAN PENAUNG TERHADAP KAPASITAS MENAHAN AIR TANAH DI KEBUN KOPI RAKYAT SUMBERMANJING WETAN - Endah Umu Nur Holisah; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Coffee is one of the farm commodities which is a source of national income and foreign exchange for Indonesia. One of the successes in the production of coffee plants is climatic conditions because it has an important role related to the water needs of plants. The availability of soil water is closely related to the ability of the soil to hold water in the soil pores (pF) and provide water for plants. Efforts to reduce the impact of climate change are the use of shade plants which will produce many litters which affect the input of water in the soil to improve soil structure and pore distribution, which will affect the soil water holding capacity. This research was conducted from March to September 2020. The research was conducted in five fields based on differences in shade plants, namely in Sumbermanjing Wetan District, Malang. The results of this research indicate that the highest soil water holding capacity is in the PK land (cocoa shade coffee garden) both at a depth of 0-20 cm and 20-40 cm because PK land has denser shade plants so that it affects the amount of water available.